Alkylation of biomass pyrolysis oils over zeolites for sustainable aviation fuels: A comprehensive investigation of the chemistry, catalysts, and kinetics - Kim, Hanbyeol; Murali, Vishnu; Lambor, Siddhant Meenor; Park, Young-Kwon; Ha, Jeong-Myeong; Vlachos, Dionisios G.; Jae, Jungho (Elsevier BV, 2025)
Considering the growing demand for sustainable aviation fuels (SAFs) to mitigate the environmental impact of the aviation sector, this study explored alkylation for converting biomass pyrolysis oil into SAF precursors. More specifically, alkylation extends the carbon chain lengths of short-chain bio-oil components to C8-C15 aviation fuel-grade molecules. In the current study, the use of meso-Y zeolites with enlarged pores and strong acidity are employed for the first time as effective catalysts to significantly enhance the conversion and selectivity of long-chain hydrocarbons. To achieve the desired selectivity, we systematically optimize temperature, catalyst microstructure, alcohol structure, and reactant/solvent ratio in the alkylation process. Secondary alcohols, especially isopropanol, are optimal alkylating agents owing to their suitable reactivity and their ability to generate high-quality fuels. Moreover, the effects of the bio-oil phenolic substituents on the efficiency of the alkylation reaction were also investigated, revealing a delicate balance between steric and electronic effects. Through kinetic analysis and optimization of the reaction parameters, this study demonstrates that alkylation catalyzed by meso-Y zeolite catalysts offers a promising route for converting bio-oils into aviation fuels. This process not only addresses the requirement for sustainable fuel sources but also aligns with global carbon reduction goals. Overall, these findings contribute to a broader understanding of bio-oil upgrading technologies and provide valuable insights into the development of scalable and sustainable aviation fuel production processes.